2022
DOI: 10.3390/cells11132003
|View full text |Cite
|
Sign up to set email alerts
|

Cell–Fibronectin Interactions and Actomyosin Contractility Regulate the Segmentation Clock and Spatio-Temporal Somite Cleft Formation during Chick Embryo Somitogenesis

Abstract: Fibronectin is essential for somite formation in the vertebrate embryo. Fibronectin matrix assembly starts as cells emerge from the primitive streak and ingress in the unsegmented presomitic mesoderm (PSM). PSM cells undergo cyclic waves of segmentation clock gene expression, followed by Notch-dependent upregulation of meso1 in the rostral PSM which induces somite cleft formation. However, the relevance of the fibronectin matrix for these molecular processes remains unknown. Here, we assessed the role of the P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Recently, we showed that the fibronectin-integrin-ROCK-NM II signalling axis regulates EC dynamics in the chicken PSM. Importantly, inhibition of actomyosin-mediated contractility delayed the period of hairy1 (hes4) oscillations from 90 to 120 min (Gomes de Almeida et al, 2022), unveiling a previously unappreciated biomechanical regulation of the EC periodicity.…”
Section: Strategies For Accelerating/delaying the Embryo Clockmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, we showed that the fibronectin-integrin-ROCK-NM II signalling axis regulates EC dynamics in the chicken PSM. Importantly, inhibition of actomyosin-mediated contractility delayed the period of hairy1 (hes4) oscillations from 90 to 120 min (Gomes de Almeida et al, 2022), unveiling a previously unappreciated biomechanical regulation of the EC periodicity.…”
Section: Strategies For Accelerating/delaying the Embryo Clockmentioning
confidence: 98%
“…Recently, our lab evaluated the importance of fibronectin (FN) extracellular matrix assembly and signalling through the integrin-ROCK-NM II axis for somite segmentation and EC oscillations in chick PSM. We found that experimental treatments targeting FN matrix assembly, cell-FN interactions and actomyosin contractility significantly perturbed somite formation and EC gene expression, highlighting the importance of the PSM tissue's mechanical properties for EC oscillations (Gomes de Almeida et al, 2022).…”
Section: Cell Autonomous Vs Tissue Level Oscillationsmentioning
confidence: 98%